Ketogenic Diet Improves Core Symptoms of Autism in BTBR Mice - Ruskin, David N. (Public Library of Science, 2013)
Autism spectrum disorders share three core symptoms: impaired sociability, repetitive behaviors and communication deficits. Incidence is rising, and current treatments are inadequate. Seizures are a common comorbidity, and since the 1920’s a high-fat, low-carbohydrate ketogenic diet has been used to treat epilepsy. Evidence suggests the ketogenic diet and analogous metabolic approaches may benefit diverse neurological disorders. Here we show that a ketogenic diet improves autistic behaviors in the BTBR mouse. Juvenile BTBR mice were fed standard or ketogenic diet for three weeks and tested for sociability, self-directed repetitive behavior, and communication. In separate experiments, spontaneous intrahippocampal EEGs and tests of seizure susceptibility (6 Hz corneal stimulation, flurothyl, SKF83822, pentylenetetrazole) were compared between BTBR and control (C57Bl/6) mice. Ketogenic diet-fed BTBR mice showed increased sociability in a three-chamber test, decreased self-directed repetitive behavior, and improved social communication of a food preference. Although seizures are a common comorbidity with autism, BTBR mice fed a standard diet exhibit neither spontaneous seizures nor abnormal EEG, and have increased seizure susceptibility in just one of four tests. Thus, behavioral improvements are dissociable from any antiseizure effect. Our results suggest that a ketogenic diet improves multiple autistic behaviors in the BTBR mouse model. Therefore, ketogenic diets or analogous metabolic strategies may offer novel opportunities to improve core behavioral symptoms of autism spectrum disorders.